Dynamic Response Analysis of a Double Main Girder Cable-stayed Bridge with Asymmetric Breakage of Tension Cables - Wang Xiaoming; Deng Hua; Gao Lixiang; Qiu Hongjie; Feng Boshun; Sun Chenjing; Yang Wenjie (工程科学与技术, 2025)
ObjectiveWith the development trend of lightweight bridge structures, double girder bridges are more and more widely used in our country. However, the double main beam structure with fewer main beams and fewer crosslinks may reduce the backup load transmission path of the system, reduce the nonlinear redundancy of the system, and lead to the decline of its internal buffer performance in response to sudden disasters, and thus increase the risk of major safety accidents or even collapse of the structure. To investigate the dynamic response characteristics of large-span double main girder cable-stayed bridges under asymmetric cable breakage, a nonlinear dynamic numerical model based on fibre macrocells was established using an actual cable-stayed bridge as the research object. The AP method, based on equivalent unloading, was adopted to simulate the sudden cable breakage process. The effects of different asymmetric cable breakage scenarios on the dynamic response of the remaining structure were analysed. The dynamic impact was evaluated by calculating the dynamic amplification factors of key components.MethodsFirstly, the dynamic numerical model of the double-girder cable-stayed bridge was established by using the OpenSEES open-source program based on fiber macro elements, and was compared with the bar system model of Midas/Civil to verify the accuracy of the model. Secondly, by deriving the calculation formula of the equivalent unloading component force when the stay cable breaks off, and using the alternate path method (i.e., the AP method) based on equivalent unloading, the asymmetric breaking process of the stay cable is simulated. Finally, by calculating the dynamic response of the remaining structure and analyzing the dynamic amplification factor (i.e., DAF) of the key components, the influence law of the asymmetric fracture of the cables in the double-girder cable-stayed bridge on the dynamic response of the remaining structure and its dynamic impact effect were analyzed. Results and Discussions　The numerical models of the double-girder concrete cable-stayed bridge were established respectively by using the OpenSEES program and the Midas/Civil software. Moreover, the relative errors of the cable forces, static responses and dynamic characteristics of the bridge calculated by both were within 10%. It indicates that the nonlinear dynamic numerical model of the double-girder concrete cable-stayed bridge established based on the fiber macro element theory in this paper is accurate and reliable. By calculating the residual structural dynamic response after asymmetric fracture of the cable, it can be found that the fracture of the unilateral cable in the double-girder cable-stayed bridge causes lateral displacement and lateral torsion of the main girder, and the fracture of the mid-span long cable has the most obvious dynamic impact effect on the main girder. However, due to the constraint effect of the end support, the dynamic impact effect on the structure caused by the fracture of the side span long cable is relatively small. Furthermore, after the asymmetric fracture of the cables, the cable forces of the remaining structure of the cable-stayed bridge undergo redistribution. Moreover, the closer the remaining cables are to the position of the broken cables, the greater the change in their cable forces. However, the maximum dynamic stress of the remaining cables remains below the yield strength. Under some cable breakage conditions, the dynamic cable force of the cable at the symmetrical position of the broken cable is reduced compared with the initial cable force, and the cable force unloading phenomenon will occur. After the asymmetric fracture of the cable, the upper and lower side bridge towers of the cable-stayed bridge will undergo relative displacement. However, in most working conditions, the displacement amplification coefficients of the top of the towers on both sides are basically the same. In the case of sudden breakage of a single cable, the dynamic response of the remaining structure on the unbroken cable side is generally smaller than that on the broken cable side, but the DAF of the remaining structure on the unbroken cable side is larger, and its dynamic amplification effect is more obvious. Under the condition of partial cable damping-off, the DAF of the remaining structure exceeds 2.0, indicating that it is not conservative to evaluate the dynamic response of the remaining structure of the cable-stayed bridge after cable breakage by using the pseudo-static method and a fixed DAF.ConclusionsThe results show that the asymmetric breakage of the cable leads to the redistribution of the internal forces in the remaining structure and causes the lateral displacement and torsion of the main beam. The dynamic impact caused by the breakage of the long cables is more pronounced than that of the short cables. The maximum dynamic stress of the remaining cables stays below the yield strength. The dynamic response on the unbroken side is usually smaller than that on the broken side; however, the dynamic amplification factor is larger on the unbroken side, indicating a more significant dynamic amplification effect.